Strategi Redaksi Program Tanah Air Beta Trans TV untuk Menarik Minat Penonton - Habiburrahman Habib; Suryati Suryati; Hartika Utami Fitri (ScidacPlus, 2023)
ABSTRACT: Television is a very popular mass media in society. Almost in every public place, office, home, even in the bedroom. Therefore, any news conveyed through television media will very easily reach the middle class of society. The existence of mass media such as television, film, radio, newspapers, magazines and the internet as communication in the modern era can have a wider influence when compared to face-to-face communication. The first television in Indonesia was named TVRI (Televisi Republik Indonesia) which broadcast for the first time on August 24 1962, with a live broadcast of the opening ceremony of the Asian Games IV from the main Gelora Bung Karno stadium. Observation in general is the activity of observing an object directly and in detail to obtain correct information regarding that object. The observation activities carried out have distinctive characteristics, namely factual and systematic objectives. Observations are closely related to objects and phenomena, both causal factors and broad impacts. The definition of interview according to the Big Indonesian Dictionary (KBBI) is a question and answer session with someone who needs to be asked for information or an opinion about something. Meanwhile, according to Lexy J Moleong, an interview is a conversation with certain purposes. In this method, researchers and respondents face directly (face to face) to obtain information verbally with the aim of obtaining data that can explain the research problem. Basically, documentation is taken from English, namely Documentation, which has two meanings. First, namely presenting official information or evidence that is useful for records. Second, as an effort to record and categorize information in the form of writing, photos, videos, etc. Program monitoring and evaluation is a stage to see whether the program being broadcast is as expected or not. This monitoring and evaluation process is to determine the extent to which a plan and goal has been achieved or realized by a broadcasting station. At this stage, we will evaluate what the strengths and weaknesses were during the implementation of the program. Based on the explanation of the research results in the previous chapter, the researcher can conclude regarding the Editorial Strategy for the Tanah Air Beta Trans TV Program, namely in simple terms, mass communication can be defined as the process of communicating through mass media. . The study of mass communication is heavily influenced by the dynamics of mass media and its use by audiences. The development of mass media itself is associated with a number of factors surrounding it, for example the increasing number of literates, the rapid development of information in the economic sector, advances in technology and communication, the phenomenon of urbanization, and advertising factors